Crescimento pós-traumático em mulheres acometidas por câncer de mama: revisão sistemática da literatura - Araújo, Letielle Tonon (2013)
The concept of posttraumatic growth essentially refers to positive psychological transformations triggered by an attempt to adapt to new circumstances accruing from a traumatic event. It is a process that involves the interaction of various elements since these transformations are observed in different domains. This study s general objective was to develop a systematic review of scientific publications addressing posttraumatic growth among women afflicted with breast cancer. Data were collected from five distinct electronic databases PsycINFO, MedLine, LILACS, SciELO-Brasil and PePsic through cross-referring the terms posttraumatic growth and breast cancer and based on specific inclusion criteria. The full texts of the identified scientific publications were assessed based on a set of dimensions for analysis. Only 31, out of the 74 publications found, were selected. In general, there was a predominance of the cross-sectional design and the quantitative approach among the publications selected. The Posttraumatic Growth Inventory (PTGI) was the most frequently used instrument and mainly women with breast cancer composed convenience samples, while some studies included subgroups to enable comparisons with other populations. There was also hegemony of publications with multiple authorship, published in journals addressing papers that lie in the interface of Psychology and Health. Additionally, the University of Coimbra and McGill University stood out as the most significant centers of studies focused on the investigation of posttraumatic growth among women with breast cancer. The conclusion, considering the specific themes and results of the studies selected, is that important aspects of posttraumatic growth are satisfactorily understood while other aspects should be further explored. The fact that younger patients are more prone to posttraumatic growth is welldocumented. On the other hand, how posttraumatic growth evolves over time among women with breast cancer, especially whether and up to when positive changes covered by each of this concept s domains are maintained after the treatment is concluded, remain uncertain. Therefore, this study enabled mapping the knowledge already produced on the topic and supports its application into practice to deepen theoretical knowledge, providing elements for future research.